1978
DOI: 10.1016/0009-3084(78)90014-2
|View full text |Cite
|
Sign up to set email alerts
|

Micelle and acid-soap formation of linoleic acid and 13-L-hydroperoxylinoleic acid being substrates of lipoxygenase-1

Abstract: Surface tension measurements of linoleic acid solutions in 0.1 M sodiumborate buffer pH 10 at 23 degrees C showed that at increasing the linoleic acid concentration a sharp transition from monomers to micelles occurs at 167 micrometer. At pH 9 and 8 formation of acid-soap dimers from monomers starts at 60 micrometer and 21 micrometer respectively. The concentration range at which only monomers exist is therefore markedly reduced. For 13-L-hydroperoxylinoleic acid at pH 10 acid-soap formation still takes place,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 10 publications
5
30
0
Order By: Relevance
“…The determination of callose synthase activity revealed that the unsaturated FFAs oleic (18:1), linoleic (18:2), and a-linolenic (18:3) acids inhibited callose synthesis in in vitro as well as in planta assays at similar concentrations to those reported for soybean (Kauss and Jeblick, 1986). Moreover, the FFA concentrations were below the critical micelle concentration (Verhagen et al, 1978;Murakami et al, 1986; Sellhorn (18:3). B, FFA concentrations in wheat spikelets inoculated with F. graminearum wild type (F.g. wt) and the lipase-deficient mutant Dfgl1-2 (F.g. Dfgl1-2).…”
Section: Discussionmentioning
confidence: 93%
“…The determination of callose synthase activity revealed that the unsaturated FFAs oleic (18:1), linoleic (18:2), and a-linolenic (18:3) acids inhibited callose synthesis in in vitro as well as in planta assays at similar concentrations to those reported for soybean (Kauss and Jeblick, 1986). Moreover, the FFA concentrations were below the critical micelle concentration (Verhagen et al, 1978;Murakami et al, 1986; Sellhorn (18:3). B, FFA concentrations in wheat spikelets inoculated with F. graminearum wild type (F.g. wt) and the lipase-deficient mutant Dfgl1-2 (F.g. Dfgl1-2).…”
Section: Discussionmentioning
confidence: 93%
“…All reactions were performed at 25 O C in a 0.1 M sodium borate buffer, pH 10 (BB10). At pH 10, the critical micelle concentration of linoleate is (Verhagen et al, 1978b), and lipoxygenase-1 from soybeans has maximum activity. Reactions were carried out at final lipoxygenase concentrations of 1.3 pM or 12.5 nM; the final linoleate concentrations were 10, 50, or 100 pM.…”
Section: Methodsmentioning
confidence: 99%
“…The CMCs for 23a and 23d at the assay conditions (50 mM Tris buffer, 2 mM EDTA and 2 mM CaCl 2 , pH 7.5, R.T.) are, respectively, 628 μM and 395 μM (Figure 2B,C) which indicate that micelle formation does not occur at concentrations employed for inhibition or activation of h-5-LOX. In addition, we found a CMC value for linoleic acid of 185 μM (Figure 2A) [43], which demonstrates that the substrate concentration in the inhibition studies (100 μM) was below the CMC.…”
Section: Resultsmentioning
confidence: 99%